(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study explores the complex relationship between cultural identity and modern architectural methods, looking particularly at how tradition and modernity can live together harmoniously. Examining theoretical and practical frameworks such as Critical Regionalism and Vernacular Resilience, this course seeks to understand the challenges of maintaining cultural identity in the context of globalised architectural tendencies. This study delves at the architectural practices of renowned figures from India, Japan, the Middle East, and Africa, including Francis Kéré, Laurie Baker, and Kengo Kuma. It emphasises on how they created sustainable and culturally infused designs by using participatory methodologies, climate responsive techniques, and local materials. Educational reform, community involvement, material consciousness, symbolic continuity, and contextual design are some of the measures that have been proposed to counteract the cultural identity crisis that modernisation inevitably brings. The findings show that by analysing tradition with a critical eye, we can lay the framework for future architectural practices that are more inclusive, resilient, and innovative.